A modal approach to determine direct shear of beams subjected to impulse. (1st February 2018) - Kermani, Alireza; Ashrafi, Ali; Louhghalam, Arghavan
Highlights: A modal approach is proposed that provides accurate estimates of direct shear. The approach accounts for contribution of higher modes to the direct shear. Estimates agree closely with high-fidelity dynamic analysis. Unlike estimates based on SDOF, these estimates are not overly conservative. Abstract: Protecting important structures against blast loading is vital. Most engineering practitioners use either a Single Degree of Freedom (SDOF) approximation of the dynamic response to blast loading or a computationally expensive numerical model. In this paper, a modal approach is proposed that provides a more accurate and less conservative estimate of direct shear, the transient dynamic shear response developed within a few milliseconds of pressure wave arrival, than the estimate based on SDOF. By way of example and via the proposed approach, simple analytical expressions to estimate the direct shear are developed for simply-supported beams. The estimates are compared with the results of a series of dynamic analyses of a refined finite element model of the beam, performed using LS-DYNA. Very close agreement between the results of numerical modeling and analytical estimates are observed. In addition, the estimated direct shear is significantly lower than the value obtained from the SDOF method. The proposed approach, thus provides an efficient and accurate estimate of the direct shear to be used in structural design.